RESPONSE OF GROWTH AND YIELD OF EDAMAME SOYBEANS (Glycine max L. Merrill) IN VARIOUS DOSES OF COW MANURE AND Trichoderma harzianum - Mardevita Islami Yakti; Oktavia Sarhesti Padmini; Basuki Basuki (Jurnal Agrivet, 2019)
Edamame soybeans (Glycine max L. Merrill) is a vegetable plant which has greater benefits such as bigger seeds, sweet taste, and high protein. The innovation of fertilization technology by utilizing animal manure and Trichoderma harzianum is one of the solutions to obtain optimal and environmentally friendly result. The aim of the study was to determine the interaction, the best doses of cow manure and doses of T. harzianum to increase the growth and yield of edamame soybeans. The Research has carried out in Rejodani, Sleman, DIY in November 2018 until Februari 2019. The experiment was arranged in CRD (Completely Randomized Design) by two factor and contras orthogonal (3x3)+1. The first factor was the doses cow manure 10,15, and 20 tons.ha-1 . The second factor was the doses of inoculum T.harzianum 25, 35, and 45 grams/plant. Added control (without a combination of treatment but using inorganic fertilizers). The results showed that the doses of cow manure 15 tons/ha gave the best result on the parameters of leaf number, the number of pods, the weight of wet pods, the number of seeds, wet seed weight, and the weight of wet pods.ha-1 . The dose of T.harzianum 45 gram/plant presented the best result but not significantly different rather than T2 (35 grams/plant) on the parameter growth and yield. There was an interaction on the parameter of the weight of 100 wet seeds and the best doses on a combination P1T1 (cow manure 10 tons.ha-1 ) and T. harzianum 25 grams/plant).Keyword : Edamame soybeans, Growth, Yield, Cow manure, Trichoderma harzianum